2020
DOI: 10.1038/s41467-020-15394-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of BIN2 kinase activity by HY5 controls hypocotyl elongation in the light

Abstract: ELONGATED HYPOCOTYL 5 (HY5), a basic domain/leucine zipper (bZIP) transcription factor, acts as a master regulator of transcription to promote photomorphogenesis. At present, it's unclear whether HY5 uses additional mechanisms to inhibit hypocotyl elongation. Here, we demonstrate that HY5 enhances the activity of GSK3-like kinase BRASSINOSTEROID-INSENSITIVE 2 (BIN2), a key repressor of brassinosteroid signaling, to repress hypocotyl elongation. We show that HY5 physically interacts with and genetically acts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 60 publications
1
58
0
Order By: Relevance
“…Given the earlier discovery of a direct BIN2-BES1/BZR1 binding [ 165 ] that was recently confirmed by a single-molecular analysis [ 191 ], it is no surprise that BIN2 is also regulated by its competitive binding with other cellular proteins in plant cells. Recent studies showed that BIN2 interacted in vivo with several well-studied light signaling components, including CRY1 (Cryptochrome1, a blue-light photoreceptor) [ 192 ], the COP1 (Constitutive Photomorphogenesis1)/SPA (Suppressor of phyA-105 ) complex (a light regulated E3 ubiquitin ligase) [ 193 ], and HY5 (long hypocotyl5, a bZIP-type transcriptional factor) [ 194 ]. CRY1 exhibits a blue light-dependent binding with both BIN2 and BZR1 to enhance the BIN2-catalyzed BZR1 phosphorylation [ 192 ], thus inhibiting its nuclear translocation (likely by increased interaction with 14-3-3 proteins [ 195 ]) and its DNA binding activity through CRY1’s competitive binding to the BZR1’s DNA binding domain.…”
Section: Bin2 the Negative Regulatormentioning
confidence: 99%
“…Given the earlier discovery of a direct BIN2-BES1/BZR1 binding [ 165 ] that was recently confirmed by a single-molecular analysis [ 191 ], it is no surprise that BIN2 is also regulated by its competitive binding with other cellular proteins in plant cells. Recent studies showed that BIN2 interacted in vivo with several well-studied light signaling components, including CRY1 (Cryptochrome1, a blue-light photoreceptor) [ 192 ], the COP1 (Constitutive Photomorphogenesis1)/SPA (Suppressor of phyA-105 ) complex (a light regulated E3 ubiquitin ligase) [ 193 ], and HY5 (long hypocotyl5, a bZIP-type transcriptional factor) [ 194 ]. CRY1 exhibits a blue light-dependent binding with both BIN2 and BZR1 to enhance the BIN2-catalyzed BZR1 phosphorylation [ 192 ], thus inhibiting its nuclear translocation (likely by increased interaction with 14-3-3 proteins [ 195 ]) and its DNA binding activity through CRY1’s competitive binding to the BZR1’s DNA binding domain.…”
Section: Bin2 the Negative Regulatormentioning
confidence: 99%
“…Retention of BZR1 and BES1 in the cytoplasm depends on the interaction of their phosphorylated forms with 14‐3‐3 proteins (Bai et al ., 2007; Gampala et al ., 2007; Ryu et al ., 2007; Ryu et al ., 2010; Tang et al ., 2011). Glycogen synthase kinase 3‐mediated phosphorylation of BZR1 further reduces activity of this transcription factor by promoting its degradation (He et al ., 2002; Li et al ., 2020a). BZR1 , BES1 , and at least one other gene in the six‐member BZR family, BES1 / BZR1 HOMOLOG 4 ( BEH4 ), are involved in hypocotyl responses to BRs (He et al ., 2005; Kang et al ., 2015; Saito et al ., 2018; Galstyan and Nemhauser, 2019).…”
Section: The Central Signaling Network Regulating Hypocotyl Elongationmentioning
confidence: 99%
“…Indeed, besides phosphorylating BZRs, BIN2 exhibits kinase activity towards PIF3 and PIF4, and additionally, it has been demonstrated that Ser/Thr to Ala mutations in PIF3 or PIF4 (PIF41A mutant protein) that reduce BIN2‐mediated phosphorylation of these PIFs also stabilize both proteins (Zhao et al ., 2002; Bernardo‐Garcia et al ., 2014; Ling et al ., 2017). This suggests that BIN2 phosphorylation of PIFs promotes their degradation, as it does for BZR1, and furthermore this process appears to be important for repression of hypocotyl growth in light (He et al ., 2002; Bernardo‐Garcia et al ., 2014; Ling et al ., 2017; Li et al ., 2020a). Specifically, ProPIF4::PIF41A‐HA pif4 pif5 seedlings grown under short days (SDs; 8 h light/16 h dark) exhibit significant growth throughout the daytime, which is not observed in the wild type, ProPIF4::PIF4‐HA pif4 pif5 , or even a Pro35S::PIF4‐HA line (Bernardo‐Garcia et al ., 2014).…”
Section: Repression Of Hypocotyl and Petiole Growth By Lightmentioning
confidence: 99%
See 2 more Smart Citations